2022
DOI: 10.1111/jppi.12408
|View full text |Cite
|
Sign up to set email alerts
|

Preventing, mitigating, and managing future pandemics for people with an intellectual and developmental disability ‐ Learnings from COVID‐19: A scoping review

Abstract: Many people with an intellectual and developmental disability (IDD) are biologically, socially, and economically/politically vulnerable to developing SARS‐COV‐2 (COVID‐19) compared to the general population. Most governments have developed public‐health policies and strategies to address the challenges that COVID‐19 has presented. These policies and strategies have been based upon the general population and in fact could be detrimental to the health and well‐being of people with IDD. This paper provides a revi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 55 publications
0
26
0
Order By: Relevance
“…Research from different parts of the world has shown that adults with ID are more likely to be infected with COVID‐19 and, once infected, suffer higher rates of hospitalization and mortality (Gleason et al, 2021 ; Lunsky et al, 2022 ; Williamson et al, 2021 ). Due to higher rates of infection, mortality, and pre‐existing medical risks, much of the research and policy attention has focused on promoting safety and preventing contagion (see also Taggart et al, 2022 in this issue). Rapid changes in healthcare delivery combined with pandemic related restrictions have had a disproportionate impact on the mental health and well‐being of adults with ID, leading to an even greater number of disruptions and restrictions in their lives.…”
Section: Introductionmentioning
confidence: 99%
“…Research from different parts of the world has shown that adults with ID are more likely to be infected with COVID‐19 and, once infected, suffer higher rates of hospitalization and mortality (Gleason et al, 2021 ; Lunsky et al, 2022 ; Williamson et al, 2021 ). Due to higher rates of infection, mortality, and pre‐existing medical risks, much of the research and policy attention has focused on promoting safety and preventing contagion (see also Taggart et al, 2022 in this issue). Rapid changes in healthcare delivery combined with pandemic related restrictions have had a disproportionate impact on the mental health and well‐being of adults with ID, leading to an even greater number of disruptions and restrictions in their lives.…”
Section: Introductionmentioning
confidence: 99%
“…In the United Kingdom, a reduction of services was permitted if an individual became critically ill with COVID‐19 (Frankova, 2020 ). Media coverage has also had discriminatory undertones conveying that people with ID might not have been considered for palliative care during the pandemic (Paulauskaite et al, 2021 ; Taggart et al, 2022 ).…”
Section: Data Set 1—exploration Of Relevant Research Literaturementioning
confidence: 99%
“…Pervasive negative attitudes regarding disabilities and discrimination Taggart et al (2022)'s scoping review found that there has been a "global failure across many HIC and low-tomiddle income countries in protecting the human rights of people with an IDD during the COVID-19 pandemic." Such rights follow from the inherent dignity and worth of all human beings.…”
Section: Health Inequitiesmentioning
confidence: 99%
“…Recent scoping reviews (Doody & Keenan, 2021 ; Taggart et al, 2022 ) have synthesized research on the impact of the COVID‐19 pandemic on the health and overall well‐being of people with IDD and their caregivers. Much of this impact has been negative and shown to be disproportionate relative to the general population.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation